Kajian Kritik Seni: Transformasi Bentuk Penyajian Musik Tradisional Krumpyung Kulon Progo di Era Multimedia - Zakarias Aria Widyatama Putra; Yudhistira Oscar Olendo; Mastri Dihita Sagala (FBS Padang State University, 2023)
Traditional music, especially Krumpyung Kulon Progo, presents a different performance in the multimedia era. These differences need to be studied in the form of art criticism so that a work of art can be seen objectively. The purpose of this study is to provide a critical review of the results of the transformation of Krumpyung Kulon Progo. The method of this research study uses qualitative with an in-depth analysis approach from Edward Felman's art criticism theory, namely based on description, formal analysis, interpretation, and evaluation. The data collection stages used observation, in-depth interviews with Kulon Progo artists on krumpyung music, and written documentation. Data reliability technique using source triangulation. Data analysis uses four stages starting from data collection, data reduction, data presentation, and data conclusion. The art criticism study obtained is related to the results of the transformation in the form of Krumpyung presentation, which is a genre that changes the conception of instruments, songs, and tone systems. The instruments used by adding modern musical instruments such as electric guitar, electric bass, and drum set. Meanwhile, the songs performed are contemporary songs with changes in the nuances of the dangdut genre coupled with a diatonic tonal system. The purpose of the transformation is not to change the authenticity of Krumpyung's traditional music, but to be a persuasive step in regeneration and community support for traditional music.